Development and evaluation of a rapid and sensitive multienzyme isothermal rapid amplification with a lateral flow dipstick assay for detection of Acinetobacter baumannii in spiked blood specimens - Hu, Wei-Wei; He, Jian-Wei; Guo, Shu-Liang; Li, Jin (Frontiers in Cellular and Infection Microbiology, 2022)
Purpose: This study aimed to establish the multienzyme isothermal rapid amplification with a lateral flow dipstick (MIRA-LFD) assay and evaluate its performance in detection of A. baumannii in spiked blood specimens. Methods: The study was divided into two stages: a pilot study to establish the methodology and a clinical validation study to evaluate its performance. In the first step, we designed primers specific to detect A. baumannii, optimized the MIRA-LFD assay and analyzed its performance regarding limits of detection, reproducibility, specificity, and efficiency of detection using real-time PCR method. In the second step, we obtained 50 spiked blood isolates and detected these pathogens by MIRA-LFD assay. The MIRA-LFD time was 15 min from DNA sample amplification to complete pathogen detection. Results: The developed MIRA-LFD assay displayed a detection limit of 6 CFU/mL for detecting A. baumannii, which was significantly better than that of real-time PCR method, and no cross-reactivity was observed in other non-A. baumannii studied. The results obtained with 50 spiked blood isolates suggested that the developed MIRA-LFD assay had high specificity and sensitivity for identifying A. baumannii. Conclusions: This study demonstrates that the established MIRA-LFD assay is time-saving, more effective and sensitive, which may become a powerful tool for rapid and reliable diagnosis of bloodstream infection caused by A. baumannii in primary hospitals.